Status Kesehatan Remaja Perempuan yang Mengalami Perkawinan Anak - Ratnaningsih, Muliani; Utami, Rahayu; Waksi, Fajar (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Indonesia was one of ten countries with the highest child marriage rate, and second highest in ASEAN after Cambodia. According to data, South Sulawesi was province with the 4th position contributing to the marriage of children in Indonesia. In South Sulawesi, age of marriage less than 14 years is 0.5 percent, while age of marriage between 15 years to 19 years is 33.5 percent. Objective: This research aimed to know health status of adolescent girls who have conducted child marriage in Makassar City. Method: This research used descriptive research with quantitative approach. The variables in this research health status from child and mother. The population in this study were all girls aged 15-24 years that chosed by Snowball Sampling nonrandom method with sample size 101 girls. Results and Discussion: Health status in this study form mother and child. For mother, Body Mass Index (BMI) category owned by adolescent girls who experience child marriages, underweight 18 people (17.8%), ideal body weight 66 people (65.3%), and overweight 17 people (16.8%). For child, the status of the weight of the first child at birth, low birth weight (LBW) 8 people (9.9%), not experience LBW 73 people (90.1%). Conclusion: The description of the health status of adolescent girls shows some things that are not good for the health of adolescent girls that can be reviewed in terms of two things, namely the condition of the mother and the condition of the child. The most influential health conditions are the nutritional status of children, immunization of children, nutritional status of mothers, and some knowledge about reproductive health that is still low. Keywords: children; health; marriage; status